History and architectural importance of the House of Jarava - Barrera Camarena, Henry (2023)
One of the most outstanding built monuments in the historic center of Lima is the Jarava house, also known as Pilate's house (today the seat of the Constitutional Court). Despite the centuries that have passed since it was built, a good part of its architectural originality and artistic elements can still be seen. Among them, the two noble coats of arms made of stone and from the 17th century located in the upper part of the façade.On the other hand, through the use of a primary source, the evolution of the farm from the mid-seventeenth century to the end of the 20th century is rescued, including the different owners it had and an analysis of the version given by Ricardo Palma around the name “Pilates” that he gave to the house. In this way, we seek to emphasize the historical value it possesses and the importance of its conservation. On the other hand, through the use of a primary source, the evolution of the farm from the mid-seventeenth century to the end of the 20th century is rescued, including the different owners it had and an analysis of the version given by Ricardo Palma around the name “Pilates” that he gave to the house. In this way, we seek to emphasize the historical value it possesses and the importance of its conservation.